Variation in the quality of regional child welfare services - Morten Henningsen; Tom Kornstad (Statistics Norway, Research Department, 2012)
While child welfare services of high quality are very important for many children, measuring quality is not a simple task. This paper presents a method for estimating differences in the quality of local child welfare services. We identify the contributions of municipalities to high school completion and employment of youth who have used child welfare services. By controlling for family background and by introducing non-users to eliminate common regional effects, we hope to eliminate effects that cannot be attributed to child welfare services. Our findings may then be interpreted as mainly quality differences between the child welfare services of different municipalities. According to our results there are substantial differences in the quality of local child welfare services in Norway, and large municipalities performed systematically better than smaller ones when the outcome is high school completion.
Keywords: H75; I38; J13; 330; Child welfare; public services; high school graduation; labour market participation